2013
DOI: 10.1177/0956462413479897
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous candidiasis caused by Candida glabrata in a HIV/AIDS patient

Abstract: Cutaneous Candida infections may occur in patients with HIV/AIDS, cancer, receiving chemotherapy and solid organ transplantation. A 32-year-old woman was admitted to the department suffering from pruritic and erythematous plaque on left side of her face for the past two months. The patient was HIV positive, diagnosed five years previously, and had been on antiretroviral therapy (tenofovir/emtricitabine and lopinavir/ritonavir) for a year. She was not compliant with the medication. Elevated HIV RNA load and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…This endangers individuals with immunosuppressive diseases such as HIV/AIDS. Although oral candidiasis is one of the most common dermatological diagnoses in AIDS patients, nonmucosal candidiasis may also occur [29,30]. For example, Muñoz-Pérez et al evaluated dermatological conditions in 1161 patients with HIV-1 and found 28 patients with candidal folliculitis, 16 with candidal intertrigo, and 9 with candidal nail infection [29].…”
Section: Immunosuppressive Factorsmentioning
confidence: 99%
“…This endangers individuals with immunosuppressive diseases such as HIV/AIDS. Although oral candidiasis is one of the most common dermatological diagnoses in AIDS patients, nonmucosal candidiasis may also occur [29,30]. For example, Muñoz-Pérez et al evaluated dermatological conditions in 1161 patients with HIV-1 and found 28 patients with candidal folliculitis, 16 with candidal intertrigo, and 9 with candidal nail infection [29].…”
Section: Immunosuppressive Factorsmentioning
confidence: 99%
“…Of this number, C. albicans, C. glabrata, C. krusei, C. parapsilosis and C. tropicalis are the five most common. Most infections are induced by yeast of the Candida genus which were previously present in the body (endogenous infections), and disturbance of the balance between yeasts and host contributes to the disease process [2].…”
Section: Introductionmentioning
confidence: 99%
“…Candida species are the second factors of dermatomycoses (1). Cutaneous Candida infections may occur in patients with HIV/AIDS, cancer, receiving chemotherapy, antibiotics, steroid therapy and solid organ transplantation (2).…”
Section: Introductionmentioning
confidence: 99%